Proteomic landscape of seminal plasma associated with dairy bull fertility. Issue 1 (December 2018) - Viana, A.; Martins, A.; Pontes, A.; Fontes, W.; Castro, M.; Ricart, C.; Sousa, M.; Kaya, A.; Topper, E.; Memili, E.; Moura, A.
Abstract Male fertility is the ability of sperm to fertilize the egg and sustain embryo development. Several factors determine the fertilizing capacity of mammalian sperm, including those intrinsic to sperm and components of the seminal plasma. The present study analyzed the seminal fluid proteome ofBos taurus and potential associations between proteins and fertility scores. Mass spectrometry coupled with nano HPLC allowed the identification of 1, 159 proteins in the dairy bull seminal plasma. There were 50 and 29 seminal proteins more abundant in high (HF) low fertility (LF) bulls, respectively. Based on multivariate analysis, C-type natriuretic peptide, TIMP-2, BSP5 and sulfhydryl oxidase indicated relationship with HF bulls. Clusterin, tissue factor pathway inhibitor 2, galectin-3-binding protein and 5′-nucleotidase were associated with LF bulls. Abundance of NAD(P)(+)-arginine ADP-ribosyltransferase, prosaposin and transmembrane protein 2 proteins had the highest positive correlations with fertility ranking. Quantities of vitamin D-binding protein, nucleotide exchange factor SIL1 and galectin-3-binding protein showed the highest negative correlations with fertility ranking. A fertility ranking score was calculated and the relationship with these proteins was significant (Spearman's rho = 0.94). The present findings represent a major and novel contribution to the study of bovine seminal proteins. Indicators of fertility can be used to improve reproductive biotechnologies.